Asean plus guidelines: management of diabetic foot wounds - Soegondor, Sidartawan; Adam, John M.F; Nair, Harikrisna K.R.; Zulkifly, Ahmad Hafiz (Smith & Nephew Singapore Pte Ltd, 2014)
a reference guide on best practices in the management of diabetic foot wound